The Role of Political Affiliation in Improving Company Performance: Evidence in Southeast Asian Countries - Albertus Henri Listyanto Nugroho (Wahana Riset Akuntansi, 2023)
Purpose – This study aims to determine the relationship between political affiliation and company performance. This research uses resource-based view theory to explain the phenomenon of political affiliation and company performance in the context of three developing countries in ASEAN.Design/methodology/approach – The sample of this study covered three countries in Southeast Asia, namely Indonesia, Malaysia, and Thailand in the period 2010–2019 with a total of 3,744 observations. This study uses quantitative methods with Generalized Least Square (GLS) testing to ensure that the research model is the best linear unbiased estimation (BLUE).Findings – The results show that political affiliation has a significant positive relationship with the company's performance in terms of profit margins. The company utilizes its external resources because internal resources have not significantly impacted amid economic uncertainty. This is done to ensure that the company gets business performance and sustainability.Originality/value – This research provides updates of political affiliation in the context developing countries in ASEAN. Developing countries are attractive for this examination because companies in the region face economic uncertainties and tend to have lower-to-middle range income. Through these characteristics, companies are encouraged to utilize resources that can truly provide certainty of performance and business sustainability.Research limitations/implications – First, the sample was limited to three countries in Southeast Asia so it can only capture phenomena with the same economic culture. Second, this research uses secondary data based on the company's financial statements.